Development and psychometric validation of an Urdu-language Obsessive-compulsive personality disorder scale for adults - Samia Rashid; Zaqia Bano (Khyber Medical University Journal)
Objectives: To develop and validate the Obsessive-Compulsive Personality Disorder Scale (OCPDS) for adults in the Urdu language, ensuring its reliability and psychometric soundness within the Pakistani cultural context.